Systematic Analysis and Functional Validation of Citrus XTH Genes Reveal the Role of Csxth04 in Citrus Bacterial Canker Resistance and Tolerance - Li, Qiang; Hu, Anhua; Dou, Wanfu; Qi, Jingjing; Long, Qin; Zou, Xiuping; Lei, Tiangang; Yao, Lixiao; He, Yongrui; Chen, Shanchun (Frontiers in Plant Science, 2019)
This comprehensive survey of Xyloglucan endotransglucosylase/hydrolase (XTH) and functional validation of citrus XTH genes provides new insights into the involvement of XTHs in Xanthomonas citri subsp. citri (Xcc) infection. In this study, from the genome of sweet orange, a total of 34 CsXTH genes with XTH characteristic domains were identified and clustered into groups I/II, IIIA and IIIB. Except chromosome 9, the CsXTH genes were unevenly distributed and duplicated among all chromosomes which made CsXTHs hotpot on chromosome 4. With Xcc induction, a group of citrus canker related CsXTHs were detected. To explored the relations between CsXTHs and citrus bacterial canker (CBC), we explored the role of CsXTH04, was identified as a putative candidate gene which can be up-regulated in CBC-resistant variety. CsXTH04 verified to be a secret protein and can be induced by exogenous hormones salicylic acid (SA) and methyl jasmonate (MeJA). Over-expression of CsXTH04 confers marked CBC susceptibility to transgenic citrus, whereas the silencing of CsWAKL08 confers CBC resistance. Over all, the expert annotation of CsXTH family provides an initial basis for the functional and evolutionary study of this family while the potential CBC susceptible gene CsXTH04, validated in this study, can be used in citrus breeding to improve the CBC resistance.